Avances en la amortiguación de los efectos de la declaración de nulidad de los planes (de nuevo sobre la anulación de los planes de ordenación) - José Suay Rincón (Revista Vasca de Administración Pública)
This study dwells on the exam of the main elements on which the judicial response to the problems of challenging urban development plans is based. It reviews the legislative initiatives taken so far and those that are currently under way to cushion the spillover effects caused by the annulment of plans. And, finally, it focuses on the most recent judicial decisions in order to highlight the progress resulting from the case law of the Supreme Court.